Academic Manuscripts In Several Countries: As The Basis For Regulation Formation - Alfaris, Muhammad Ramadhana (Academos, 2024)
Hence, academic manuscripts fundamentally strive to offer a cognitive framework for crafting laws that are not driven by pseudo-interests, pseudo-needs, or pseudo-thinking. Nonetheless, the presence of academic manuscripts necessitates meticulous attention to their creation. This research aims to explore academic manuscripts in several countries regarding the formation of state regulations. The research method employs a normative juridical research type with case, conceptual, and regulation approaches. Another research approach is the comparative approach between Indonesia and other countries. The research findings explain that Overall, academic manuscripts make a highly valuable contribution to the process of forming regulations in a country by providing the knowledge, analysis, and recommendations needed for policymakers to make informed and effective decisions. In Indonesia, there is still ambiguity regarding the substance of regulations and the creation of academic manuscripts, thus affecting the regulations that are made. Meanwhile, in the European Union, Idaho, and Korea, the alignment between academic manuscripts and regulations is emphasized, with the creation of academic manuscripts overseen by academic institutions tasked with research and knowledge development. This has implications for both regulations and society